BERJUANG DENGAN MELODI: MUSIK BANYUWANGIAN SEBAGAI MEDIA REVITALISASI IDENTITAS USING - Endrayadi, Eko Crys; Nawiyanto (Balai Pelestarian Kebudayaan Wilayah X, 2019)
This paper discusses the Using community’s effort to fight for its identity through Banyuwangian music by employing the historical method. Banyuwangian music is a form of cultural expression and identity symbols of Using community. The involvement of the Banyuwangi artists in Lekra organization that led to the arrest of the artists and the prohibition of Banyuwangian music at the beginning of the New Order, at once have formed a negative image of Using community. Through Banyuwangian music, Using artists seek to put an element of creativity and modernity in musical genre, thus becoming social media and culture to fight for Using identity. A harmonious blend of ecological and cultural elements in the Banyuwangian musical elements have led to the emergence of various Banyuwangianmusic genres that are acceptable to society at large and become the identity revival era of Using parallel with other communities. Banyuwangian music is very interesting to study because of the practice of music of ethnic groups in relation to the national level to represent local interests in the realm of culture. Local popular music rarely crosses the ethno-linguistic boundaries. However, the Banyuwangian music could break down the barriers of subaltern and become the media of Using community in achieving an equal identity.